METHODOLOGICAL ASPECTS OF DEVELOPING ANALYTICAL THINKING IN FUTURE TEACHERS BASED ON THE HYPOTHETICAL-DEDUCTIVE APPROACH (Scientific journal of the Fergana State University, 2024)
Based on the hypothetical-deductive approach, theoretical-methodological foundations of developing analytical thinking in future pedagogues, ways of improving the system of developing analytical thinking, effectiveness of developing analytical thinking are studied in the article. Methodological aspects of developing analytical thinking in future teachers were also analyzed based on the hypothetical-deductive approach.